Keanekaragaman Tumbuhan Berpotensi Obat Di RPH Sekar Kabupaten Malang - Purity Sabila Ajiningrum; Aisah Erviana (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2022)
The purpose of this study was to determine the value of the index of biodiversity and the value of the important index of medicinal plants that exist in the protected forest of RPH Sekar Malang. This study used the plot line method and was carried out in stages, namely sampling, determining the location path that had been surveyed and making measuring plots consisting of 8 plots with a distance of 100 m between plots with a plot size of 20m x 20m. The research data were analyzed using the diversity value index, vegetation analysis and descriptive utilization. Based on the results of the identification and determination of potential medicinal plants, 8 species of medicinal plants were found. The total number for the diversity value index is 1. This indicates that the medicinal plant diversity index in the RPH Sekar protected forest area is in the moderate category. The importance value index for the seedling category showed the highest yield in Piper aduncum of 20.167, the stake category was Centella asiatica with the highest score of 2.899 and for the pole and tree category the largest was shown in the same species, Dendrocnide stimulant with a pole value of 6.771 and a tree value of 13.15. Keywords; Diversity, Protected Forest, Medicinal Plants